Synthesis and physical-chemical properties of 3-(alkylthio)-4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazoles - O. A. Suhak; O. I. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Aim. Selection, synthesis and biological properties of new compound play major role in creating original medicines.